Fuzzy Normed Linear Spaces Generated By Linear Functionals - Ali Reza Khoddami; Fatemeh Kouhsari (Sahand Communications in Mathematical Analysis)
For a nonzero normed linear space X, we will define some different classes of fuzzy norms on X generated by linear and bounded linear functionals. Also separate continuity of the elements within each class are investigated. The aim of this research is to introduce a source of examples and counterexamples in the field of fuzzy normed spaces.